A Study On Proxenus Hennia Swinhoe And Nymphula Responsalis Walker As Potential Biological Control Agents Of Water Lettuce (Pistia Stratiotes L.) - Kasno, , (1982)

(untitled)
Suatu pencarian binatang bertubuh ruas pemakan rumpai air kiyambang (Pistia stratiotes L.) telah dilakukan di beberapa tempat dalam kawasan Negeri Pulau Pinang dan Kuala Kedah, Malaysia. Adapun matlamat dari pada pencarian tersebut adalah untuk menemukan sebarang binatang bertubuh ruas yang mampu mengawal pertumbuhan kiyambang tersebut. Di antara sebanyak binatang bertubuh ruas yang diperolehi, Proxenus hennia Swinhoe (Lepidoptera: Noetuidae) ,dan Nymphula responsalis Wlk. (Lepidoptera: Pyralidae) ,merupakan serangga yang terpilih untuk dikaji lebih lanjut. A search for arthropods attacking water lettuce (Pistia stratiotes L.) was carried out, at some locations on Penang Island and Kuala Kedah, Malaysia The objective of the search was to look for appropriate candidate biological control agents of this aquatic weed. Several arthropods were found attacking the weed, amongst them, were Proxenus hennia Swinhoe (Lepidoptera: Noctuidae) ,and Nymphula responsalis Wlk. (Lepidoptera: Pyralidae)~ both of which were selected for further studies.